Implications of Lifting the Open-Pit Mining Ban in the Philippines - Ludwig John H. Pascual; Sonny N. Domingo; Arvie Joy A. Manejar (Philippine Institute for Development Studies (PIDS), 2022)
An order "Banning the Open-pit Method of Mining for Copper, Gold, Silver, and Complex Ores in the Country" was issued by the Department of Environment and Natural Resources (DENR) on April 27, 2017. Justifications to the order included the past environmental disasters caused by mining operations, which were then employing the open-pit mining method and indicated that such mining method poses risks to host communities and to the environment. The order affects prospective mining projects that would employ the open-pit mining method. On December 23, 2021, the ban was lifted on the premise that the "Revitalization of the Mineral Resource Industry as One Measure to Achieve Economic Growth Amidst the Crisis Caused by the COVID-19 Pandemic." The rationale behind opposing development perspectives/sentiments on open-pit mining was reviewed and the ecological integrity implications related to open-pit mining was discussed. Facts were cited and challenges or highlevel opportunities for improvement on various aspects of regulating mining activities, in general, were flagged. The method of mining (i.e. surface/open pit or underground) and type of commodity extracted (i.e. metallics, non-metallics were emphasized as not the only major factors to cause unacceptable outcomes from mining, such as potentials for environmental disasters or negative impact to social welfare. Two major directions to take were provided and options moving forward in order to optimize benefits from approved mining projects were enumerated.
Keywords: 330; open-pit mining; tailings management; governance; benefit cost analysis; environmental valuation; social impact; equitable distribution; fair share; fiscal regime